Landasan Ontologis dalam Pengembangan Kurikulum PAI pada Mata Pelajaran Al-Qur’an Hadist di Madrasah Tsanawiyah - Kafi, Muhammad Kafnun; Rosadi, Adi (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study examines the critical role of ontological foundations in the development of the Islamic Religious Education (PAI) curriculum, specifically for Qur'an and Hadith subjects in Madrasah Tsanawiyah (MTs). Recognizing the importance of a strong philosophical underpinning in religious education, this research aims to explore how integrating ontological principles into the PAI curriculum can enhance students' comprehension of Islamic values and their engagement in the learning process. Employing a qualitative research design, data were collected through in-depth interviews, observations, and document analysis at several MTs in Yogyakarta over a two-month period. The findings reveal that embedding ontological concepts in the curriculum not only deepens students' understanding of Islamic teachings but also fosters greater spiritual and character development. The study suggests that a more philosophically integrated approach to curriculum design can significantly contribute to the holistic development of students, aligning educational practices with the core values of Islam. The implications of this research highlight the need for educational institutions to adopt and implement curricula that emphasize deep, reflective learning, which is essential for cultivating both intellectual and spiritual growth in students.